Oxford international primary 4: English student book - Danihel, Emma; Hearn, Izabella (Pakistan : Oxford university press, 2022)
The Oxford International Primary English Student Book 4 for the Pakistan edition is designed to enhance students' English language skills through engaging and age-appropriate content. It focuses on developing reading, writing, speaking, and listening abilities. The book includes diverse texts such as stories, poems, and informational passages, alongside activities that encourage comprehension and creativity. It also integrates vocabulary building and grammar exercises to support language acquisition. The content is tailored to align with international educational standards while being relevant to the Pakistani context.
Keywords: English - Text Book